2015
DOI: 10.1038/srep13005
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant compound tert-butylhydroquinone activates Akt in myocardium, suppresses apoptosis and ameliorates pressure overload-induced cardiac dysfunction

Abstract: Tert-butylhydroquinone (TBHQ) is an antioxidant compound which shows multiple cytoprotective actions. We evaluated the effects of TBHQ on pathological cardiac remodeling and dysfunction induced by chronic overload. Pressure overload was created by transverse aortic constriction (TAC) in male C57BL/6 mice. TBHQ was incorporated in the diet and administered for 4 weeks. TBHQ treatment prevented left ventricular dilatation and cardiac dysfunction induced by TAC, and decreased the prevalence of myocardial apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…Associated with Nrf2 induction in diabetic mouse aorta, tBHQ treatment reduced the area, extension, lipid content and inflammatory milieu of atherosclerotic plaques, independently of changes in blood glycemia and lipids. Our results are in agreement with the previously reported effect of tBHQ in ischemic stroke ( Shih et al, 2005 ) and cardiac dysfunction ( Zhang et al, 2015 ) and support the use of Nrf2 activators as potential therapy for diabetic complications ( Xue et al, 2008 ; Jiang et al, 2010 ; Tan and de Haan, 2014 ; Tan et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Associated with Nrf2 induction in diabetic mouse aorta, tBHQ treatment reduced the area, extension, lipid content and inflammatory milieu of atherosclerotic plaques, independently of changes in blood glycemia and lipids. Our results are in agreement with the previously reported effect of tBHQ in ischemic stroke ( Shih et al, 2005 ) and cardiac dysfunction ( Zhang et al, 2015 ) and support the use of Nrf2 activators as potential therapy for diabetic complications ( Xue et al, 2008 ; Jiang et al, 2010 ; Tan and de Haan, 2014 ; Tan et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…Neuroprotective actions have been also reported in experimental models of traumatic brain injury ( Saykally et al, 2012 ; Chandran et al, 2017 ), Alzheimer’s disease ( Akhter et al, 2011 ), and neonatal hypoxic-ischemic brain damage ( Zhang et al, 2018 ). Moreover, tBHQ ameliorates overload-induced cardiac dysfunction by suppressing apoptosis and promoting autophagy ( Lin et al, 2014 ; Zhang et al, 2015 ), and also improves angiogenesis and heart function in a model of myocardial infarction ( Zhou et al, 2017 ). tBHQ results from butylated hydroxyanlisole biotransformation, and readily auto-oxidizes to an electrophilic metabolite, tert-butylbenzoquinone (tBQ).…”
Section: Introductionmentioning
confidence: 99%
“…We conclude that other mechanisms besides Nrf2 and IL-17D could regulate certain innate immune cell infiltration after tBHQ injection. Other studies have found that tBHQ can also activate Akt 26 and its downstream target endothelial nitric oxide synthase (eNOS) 27 . It is possible that tBHQ acts through one of these or another yet unknown pathway in our system.…”
Section: Resultsmentioning
confidence: 99%
“…Independently of Nrf2 activation, other protective mechanisms of tBHQ are also involved in the induction of autophagy ( 44 , 45 ). In addition, a recent study demonstrated that tBHQ activated Akt rather than Nrf2 to suppress apoptosis ( 46 ). In our study, pre-treatment with tBHQ significantly restored the level of Nrf2 protein ( Fig.…”
Section: Discussionmentioning
confidence: 99%